1999
DOI: 10.1046/j.1460-9592.1999.00395.x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative extradural infusions in children: preliminary data from a comparison of bupivacaine/diamorphine with plain ropivacaine

Abstract: To try to decrease the incidence of side-effects associated with postoperative extradural infusions of local anaesthetics in combination with opioids, we have used plain ropivacaine solutions in 200 children. The first 72 children received an infusion of bupivacaine 0.125% + diamorphine 20 microg x ml-1, then 200 children received plain ropivacaine solutions. The children who received ropivacaine were found to have lower incidences of nausea, pruritus, urinary retention, and were less sedated, despite comparab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…32 The recovery of bowel function was significantly faster in the epidural group at T 12 to T 72 in our study. Moriarty et al had shown lower incidences of nausea/vomiting and pruritus in children receiving epidural ropivacaine compared with those receiving an epidural bupivacaine/ hydromorphine mixture.…”
Section: Discussionsupporting
confidence: 46%
“…32 The recovery of bowel function was significantly faster in the epidural group at T 12 to T 72 in our study. Moriarty et al had shown lower incidences of nausea/vomiting and pruritus in children receiving epidural ropivacaine compared with those receiving an epidural bupivacaine/ hydromorphine mixture.…”
Section: Discussionsupporting
confidence: 46%
“…Morphine or fentanyl has been used most frequently in neonates and infants 22,25,30 , but the use of a wide range of opioid drugs has been reported in children 6 months and older including: alfentanil 112 , sufentanil 113115 , buprenorphine 116 , butorphanol 117119 , diamorphine, 120,121 , hydromorphone 122 and tramadol 103,123–127 . In surveys of UK pediatric anesthetists, 85% used opioids for epidural analgesia 77 , but variability in the agent chosen (fentanyl, morphine, or diamorphine) was noted in this and an earlier survey (21% adding fentanyl and 13% adding diamorphine to caudal anesthetic blocks) 109 .…”
Section: Clinical Choice Of a Spinal Analgesic: Efficacymentioning
confidence: 99%
“…Moriarty et al . also studied ropivacaine in continuous infusion postoperatively, comparing 0.2% ropivacaine, 0.25% ropivacaine and 0.125% bupivacaine plus diamorphine at an infusion rate of 0.1–0.3 ml·kg –1 ·h –1 (32). They found the same analgesic efficacy but a greater incidence of side‐effects with the association of bupivacaine and morphine.…”
Section: Ropivacaine Clinical Studiesmentioning
confidence: 99%